2021
DOI: 10.3390/plants10102090
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Plant Richness, Biogeographical Composition, and Life Forms along an Elevational Gradient in a Mediterranean Mountain

Abstract: Despite the increasing interest in elevational patterns in biodiversity, few studies have investigated variations in life forms and biogeographical composition, especially in the Mediterranean biome. We investigated elevational patterns in species richness, biogeographical composition (chorotypes) and life forms (Raunkiaer classification) along an elevational gradient in a Mediterranean mountain (Central Italy). We found a general hump-shaped pattern of species richness, which can be explained by harsher condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 110 publications
2
17
0
Order By: Relevance
“…Factors directly related to elevation (e.g., temperature, rainfall, light intensity, nitrogen availability) are indicated as the main factors that regulate the distribution and number of taxa [189,190]. Despite most of the studies on species richness variation along elevational gradients found either a monotonic decline with increasing elevation or a hump-shaped pattern with a mid-elevational peak [191][192][193], the presence of high mountains favors the processes of plant speciation. Indeed, in recent years, many species were discovered or described for mountain areas also in Italy [194][195][196].…”
Section: Exploration Of Floristic Similarities Between Regionsmentioning
confidence: 99%
“…Factors directly related to elevation (e.g., temperature, rainfall, light intensity, nitrogen availability) are indicated as the main factors that regulate the distribution and number of taxa [189,190]. Despite most of the studies on species richness variation along elevational gradients found either a monotonic decline with increasing elevation or a hump-shaped pattern with a mid-elevational peak [191][192][193], the presence of high mountains favors the processes of plant speciation. Indeed, in recent years, many species were discovered or described for mountain areas also in Italy [194][195][196].…”
Section: Exploration Of Floristic Similarities Between Regionsmentioning
confidence: 99%
“…Ecological gradients in relation to altitude have long been a dominant theme in plant ecology. As a result, we now benefit from a wealth of studies detailing patterns in the proportion of endemic species and species diversity [ 1 , 2 , 3 , 4 ], associations among species [ 5 ], pollination strategies [ 6 , 7 , 8 ], reproductive traits [ 9 , 10 , 11 ], and potential variation in functional traits [ 12 , 13 , 14 ] along altitudinal gradients. In more recent years, the observation of changes in species distribution and their colonisation of higher latitudes and altitudes in relation to warming climates [ 15 , 16 , 17 ], have renewed interest in the understanding of the ecological interactions that govern distribution patterns in mountain plants.…”
Section: Introductionmentioning
confidence: 99%
“…At the local scale, vascular plant species richness and assemblages' diversity are influenced by meso-climate features of the different territories and their geomorphology; in particular elevation gradients and mountain distribution have a crucial role. However, there are not many papers dealing with the effects of elevation gradients on vascular plant diversity; Di Biase et al [7] sheds light on this intriguing aspect of Mediterranean plant diversity, whose importance was already underlined by Thompson [4]. Di Biase et al [7] describe the variation of the ecological (life-forms) and the geographical (chorologic types) contingents of the Mt.…”
mentioning
confidence: 99%
“…However, there are not many papers dealing with the effects of elevation gradients on vascular plant diversity; Di Biase et al [7] sheds light on this intriguing aspect of Mediterranean plant diversity, whose importance was already underlined by Thompson [4]. Di Biase et al [7] describe the variation of the ecological (life-forms) and the geographical (chorologic types) contingents of the Mt. Genzana (central Apennines, Italy) flora, showing the increase of the endemic component with the increase of the elevation.…”
mentioning
confidence: 99%
See 1 more Smart Citation